Pitfalls of Prenatal Diagnosis guiding Postnatal Management in Congenital Adrenal Hyperplasia(CAH) - Murthy, Deepa Badrinath (J Endocr Soc, 2021)
Background: 21-hydroxylase deficiency is the most common form of CAH and is associated with a variety of clinical phenotypes (salt wasting SW, simple virilizing SV and non-classic NCCAH). Commonly, there is a strong genotype-phenotype correlation for SW and NCCAH, but this is less predictable with the SV forms. We present a case with prenatal diagnosis of classic CAH which demonstrated genotype-phenotype discordance. Clinical Case: Ex 39 weeker female born to non-consanguineous parents was prenatally diagnosed with CAH based on routine genetic screen. Mother was noted to be a carrier for Intron 2G and father was a carrier of p.I172N both known to be pathogenic variants on CYP21A2. At 23 weeks gestational age, DNA analysis revealed fetus was compound heterozygous for both mutations which is most commonly associated with either SV or SW phenotype. At birth, infant had mild edema of the labia majora which resolved; the clitoris was not enlarged. There was no genital virilization or urogenital sinus. Newborn screen sent at 15 hours of life:17 OHP 132 ng/ml, repeat on DOL 3:77 ng/ml and DOL 13:59.9 ng/ml. High dose cosyntropin stim test on DOL 3 at 0 min: Cortisol not done, 17 OHP 1279 ng/dl; 60 min: Cortisol 12.3mcg/dl, 17OHP 3394 ng/dl. DOL 5 at 0 min: Cortisol 2.7 mcg/dl, ACTH 164.5 pg/ml, 17OHP 803.7 ng/dl; 60 minute: Cortisol 7.6mcg/dl, 17OHP 5920 ng/dl. Using available 17OHP normograms, the infant’s stimulated 17 OHP levels were not consistent with classic CAH. Unstimulated testosterone on DOL 3: 25ng/dl, DOL 5: 14 ng/dl. Ultrasound showed adrenal gland thickness 4mm bilaterally (upper limit of normal). Hydrocortisone (HC) was started on DOL 5 at 35 mg/m2/day after the stim test. On DOL 7, HC was increased to 100 mg/m2/day; fludrocortisone 0.1 mg twice daily and NaCl 0.5 g/day were started (Na 131, K 6.5, plasma renin activity 80.2). Upon discharge (DOL 13), infant was on HC 35 mg/m2/day, Fludrocortisone 0.1mg twice daily and NaCl 2g/day. Doses were adjusted accordingly during outpatient follow up. Currently infant is 4 months of age, thriving and remains on HC 11.3 mg /m2/day, Fludrocortisone 0.05 mg twice daily and NaCl 750 mg daily. Postnatal genetic analysis confirmed prenatal genotype. Conclusion: In general, genotype-phenotype correlation has 80–90% concordance. However clinicians should be aware of genotype/phenotype discrepancies that exist in order to carefully guide postnatal management based on prenatal genetic analysis. Our patient’s 17-ohp was done by LC/MS, which is standard now for most specialized endocrine laboratories. However, the 17-ohp nomograms for CAH, which are frequently used for subtype categorization, are based on RIA levels. Further studies would be helpful in creating an updated normogram using LCMS specifically for the neonatal period, as confirmatory screening of CAH will become more common with the rise in parental prenatal carrier screening.